The Impact of Digital News Media Integration within Problem-Based Learning on Students' Critical Thinking Skills and Learning Outcomes in Vocational Science Education - Rahmi Lifia Citra; Fetri Yeni J; Darmansyah; Rayendra (Postgraduate, University of Mataram, 2026)
This study aims to investigate the impact of integrating digital news media as an authentic problem trigger within the Problem-Based Learning (PBL) model on students' critical thinking skills and cognitive learning outcomes in vocational science education (PIPAS). This research employed a quasi-experimental approach with a nonequivalent control group design at SMKN 1 Batam. Data were collected through pre-tests and post-tests structured to measure Robert H. Ennis' critical thinking indicators and cognitive achievements, which were then analyzed using descriptive statistics and independent sample t-tests. The descriptive analysis revealed that the experimental group achieved an average N-gain score of 0.32 in the moderate category for critical thinking skills, outperforming the control group which scored 0.10 in the low category. A similar trend occurred in cognitive learning outcomes, where the experimental group secured an N-gain score of 0.37 (moderate) compared to the control group's score of 0.15 (low). Furthermore, the independent sample t-test confirmed that this difference was statistically significant, yielding a t-value of 2.389 with a significance level of p = 0.01 (p < 0.05). The integration of dynamic, ill-structured problems from digital news portals successfully stimulated vocational students' analytical thinking, reflection, and problem-solving capacities. In conclusion, incorporating digital news media within the PBL framework is a highly effective instructional strategy to foster critical thinking and academic achievement in vocational science streams.